Indonesia-Russia Strategic Partnership in Southeast Asia Region - Hendra Manurung (Jurnal Ilmiah Hubungan Internasional, 2021)
This paper aims to elaborate Indonesia and Russia bilateral relations, which closer post March 2018, after both countries leaders in Moscow agree accelerating the draft of the new strategic partnership agreement. Foreign Ministers Retno Marsudi and Sergey Lavrov signed a Plan of Consultation 2017 to 2019 pursued at bilateral interactions intensification. Kremlin views Jakarta as regional influential power and able to become dominant regional actor in Southeast Asian. This paper revealed, through Russia with ASEAN dialogue partnership, thus, a road map under working framework in strengthening closer relations along with mutual benefits pursued by Jakarta and Moscow also should be implemented and proceed further.